2015
DOI: 10.1093/nar/gkv258
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic regulation of intragenic transposable elements impacts gene transcription in Arabidopsis thaliana

Abstract: Genomes of higher eukaryotes, including plants, contain numerous transposable elements (TEs), that are often silenced by epigenetic mechanisms, such as histone modifications and DNA methylation. Although TE silencing adversely affects expression of nearby genes, recent studies reveal the presence of intragenic TEs marked by repressive heterochromatic epigenetic marks within transcribed genes. However, even for the well-studied plant model Arabidopsis thaliana, the abundance of intragenic TEs, how they are epig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
97
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(104 citation statements)
references
References 61 publications
(96 reference statements)
6
97
0
1
Order By: Relevance
“…Plant genomes contain numerous TEs that are often silenced by epigenetic changes, such as histone modifications and DNA methylation. Although TEs can be a target of epigenetic silencing to prevent the expression of TE genes, the epigenetic regulation of TEs can also affect the expression of nearby genes, adding complexity to their transcriptional control (35,36). The association of DmCs and DMRs located in TEs that are inserted within gene features [generelated transposable elements (GR-TEs)] showed that, although there was a slight predominance of hypermethylation (57 hyperDMRs, 431 hyper-DmCs) over hypomethylation (31 hypo-DMRs, 369 hypo-DmCs), this tendency was consistent only for TEs located in DEGs (Fig.…”
Section: Analysis Of Methylomes In the Presence Of Pi Starvation Provmentioning
confidence: 99%
“…Plant genomes contain numerous TEs that are often silenced by epigenetic changes, such as histone modifications and DNA methylation. Although TEs can be a target of epigenetic silencing to prevent the expression of TE genes, the epigenetic regulation of TEs can also affect the expression of nearby genes, adding complexity to their transcriptional control (35,36). The association of DmCs and DMRs located in TEs that are inserted within gene features [generelated transposable elements (GR-TEs)] showed that, although there was a slight predominance of hypermethylation (57 hyperDMRs, 431 hyper-DmCs) over hypomethylation (31 hypo-DMRs, 369 hypo-DmCs), this tendency was consistent only for TEs located in DEGs (Fig.…”
Section: Analysis Of Methylomes In the Presence Of Pi Starvation Provmentioning
confidence: 99%
“…This model called the “rheostat hypothesis” was demonstrated in vitro but direct evidence for it is limited. More recently, methylation status of intronic TEs in Arabidopsis thaliana was correlated with lower transcription of genes with TE insertions [53]. …”
Section: Retrotransposon-induced Changes In Genome Regulationmentioning
confidence: 99%
“…One exception is the genome of Arabidopsis, which contains relatively few intronic TEs. A recent analysis estimated that only 0.7% of annotated genes in the Arabidopsis genome contain intronic TEs (Le et al, 2015). However, genome organization of Arabidopsis is exceptional; most plant species have a large number of TEs within introns.…”
Section: Control Of Intragenic Heterochromatinmentioning
confidence: 99%
“…That is the case for intronic TEs in both maize and A. lyrata. Even in the exceptionally compact genome Arabidopsis, long introns often contain non-CpG methylation, mainly associated with TE insertions there (Saze et al, 2013;Le et al, 2015;Fig. 1).…”
Section: Control Of Intragenic Heterochromatinmentioning
confidence: 99%
See 1 more Smart Citation